Health Implications of COVID-19 for New Generations: From Physical to Mental Health Challenges - Grzelak, Alicja; Langner, Sara (Quality in Sport, 2024)
Introduction: The COVID-19 pandemic has left a lasting impact on global health, affecting not only physical well-being but also mental and emotional health. New generations face unique challenges, shaped by disrupted lifestyles, prolonged isolation, and evolving healthcare needs. These implications demand a comprehensive understanding of both immediate and long-term health outcomes. Purpose of Work: This paper explores the multifaceted health impacts of COVID-19 on new generations, emphasizing physical, mental, and social dimensions. By synthesizing current research, the study seeks to highlight key challenges and propose strategies for addressing these health concerns. State of Knowledge: Emerging evidence reveals a dual burden of physical and mental health issues in younger populations. Long COVID symptoms, reduced physical activity, and developmental delays are prominent physical concerns. Simultaneously, heightened levels of anxiety, depression, and emotional stress reflect the pandemic’s toll on mental health. Socioeconomic disparities further exacerbate these outcomes, while digital reliance during the pandemic has introduced new behavioral patterns requiring attention. Material and methods: This study utilized a systematic literature review methodology, involving a search across prominent scientific databases like PubMed and Google Scholar, followed by a rigorous screening process to identify relevant studies for in-depth examination. Summary: COVID-19 has imposed unprecedented health challenges on new generations, blending physical ailments with pervasive mental health struggles. This paper underscores the importance of integrative health approaches and policy-driven interventions to mitigate long-term impacts. Future research must focus on preventive measures, equitable healthcare access, and innovative strategies to foster resilience and holistic recovery.